"Not One Wasted Minute": Graduate Research Rounds - Perkovic, Olga (My University, 2017)
In September 2016, McMaster University Library piloted an event for graduate students that was unlike the traditional offering of drop-in presentations or workshops. This poster will describe how a teaching “rounds” activity to present key information about the library's services, collections and resources, was planned, promoted and implemented. Graduate Research Rounds, a collaboration between the Library and the School of Graduate Studies, proved to be a worthwhile activity for both the library staff and the students. Observations and feedback will also be shared.
Keywords: graduate students, graduate research, graduate student outreach, library collections, library services, library resources